2017
DOI: 10.1007/s00705-016-3180-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the spleen proteome of chickens infected with reticuloendotheliosis virus

Abstract: Infection with reticuloendotheliosis virus (REV), a gammaretrovirus in the family Retroviridae, can result in immunosuppression and subsequent increased susceptibility to secondary infections. In the present study, we identified differentially expressed proteins in the spleens of chickens infected with the REV-A HLJ07I strain, using two-dimensional gel electrophoresis on samples from time points coinciding with different phases of the REV life cycle. Differentially expressed proteins were identified using one-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 80 publications
0
5
0
1
Order By: Relevance
“…In China, more than 20 provinces, including Shandong Province, Anhui Province, Yunnan Province, etc., have reported REV infections, with a 20–30% prevalence rate in poultry [ 4 ], emphasizing that the direct and indirect hazards to the poultry industry are becoming increasingly serious. RE characteristics, including immunosuppression, tumorigenesis, mixed infection, contaminated vaccine, and genetic recombination, which are harmful to human health, have gradually increased awareness of the disease’s significance [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In China, more than 20 provinces, including Shandong Province, Anhui Province, Yunnan Province, etc., have reported REV infections, with a 20–30% prevalence rate in poultry [ 4 ], emphasizing that the direct and indirect hazards to the poultry industry are becoming increasingly serious. RE characteristics, including immunosuppression, tumorigenesis, mixed infection, contaminated vaccine, and genetic recombination, which are harmful to human health, have gradually increased awareness of the disease’s significance [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although a certain studies on the mechanism of REV pathogenesis and immunity have focused on genome and proteome levels (Li et al, 2016 ; Xue et al, 2017 ), these processes are still poorly understood on gene expression level. This study had systematically identified the global genes and pathways by RNA sequencing in chicken lymphocytes after REV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, they also present inherent difficulties, such as the longer sample collection time, and the lack of fully annotated genomes/proteomes. One example of such a study is the reticuloendotheliosis virus infection in chickens that was initiated for a better understanding of the infection mechanisms that cause immune suppression …”
Section: Protein Expressionmentioning
confidence: 99%